The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2004
DOI: 10.1259/dmfr/26126766
|View full text |Cite
|
Sign up to set email alerts
|

Radiation exposure in dental radiology: a 1998 nationwide survey in Switzerland

Abstract: Several recommendations for dose reduction are made. These include the re-evaluation of the patterns and justification for prescribing some particular types of dental examinations as well as the avoidance of unnecessary irradiation by the use of rectangular collimation and high sensitivity F-speed films.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 20 publications
0
6
0
1
Order By: Relevance
“…However, contemporaneous data on this topic within the European Union were limited to just two studies. Of these, the study conducted in 2004 (Aroua et al. 2004) found rectangular collimation was used in 15% of Swiss dental practices, whereas, in 2005, amongst Belgium dentists (Gijbels et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, contemporaneous data on this topic within the European Union were limited to just two studies. Of these, the study conducted in 2004 (Aroua et al. 2004) found rectangular collimation was used in 15% of Swiss dental practices, whereas, in 2005, amongst Belgium dentists (Gijbels et al.…”
Section: Discussionmentioning
confidence: 99%
“…However, contemporaneous data on this topic within the European Union were limited to just two studies. Of these, the study conducted in 2004 (Aroua et al 2004) found rectangular collimation was used in 15% of Swiss dental practices, whereas, in 2005, amongst Belgium dentists (Gijbels et al 2005) only 6% of clinicians reported using this type of collimation. Several factors may have been instrumental in promoting rectangular collimation such as their recommendation within European guidelines (European Commission 2004), the simplicity of converting a circular open-ended to rectangular collimation using commercially available devices and finally knowledge of these devices garnered from several sources such as research studies in professional journals and/or attendance at courses on radiation protection.…”
Section: Contemporary Endodontic Practice Orafi and Rushtonmentioning
confidence: 99%
“…In the study carried out by Ilguly in 2005, 65.8% of dental practitioners were not aware of film speed. 4 , 5 …”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the rate of digital radiography use was 7%, which is consistent with the results reported by Ilguy and Aroua. 2 , 3 , 5 The reason for limited use of digital imaging may be its high initial cost. The advantage of automatic processing is the reduction of processing time.…”
Section: Discussionmentioning
confidence: 99%
“…Une enquête effectuée en 1998 a démontré que plus de quatre millions d'examens radiologiques dentaires sont pratiqués annuellement en Suisse, soit plus de 40 % du nombre total d'examens à rayons X ; cependant, la contribution relative à la dose collective ne dépasse pas le 1 % (Aroua et al, 2004). Cette technique permet de mettre en évidence un grand nombre de pathologies, d'évaluer la croissance et le développement de la dentition, d'obtenir des informations durant les soins et d'établir rapidement le bilan dentaire d'un patient (EC, 2004).…”
Section: Introductionunclassified